Centrosome duplication and separation in animal cells - Fry, Andrew (Henry Stewart Talks, 2009)
The centrosome as a microtubule organizing centre, Microtubule nucleation, Mitotic spindle organization, Centrosomes and ciliogenesis, Centrosome structure and composition, The centrosome duplication cycle, Regulation of centrosome duplication, Centriole formation pathways, Centriolar cohesion, Regulation of centrosome separation, Centrosome overduplication in cancer cells, Aneuploidy and chromosome instability, Models for the acquisition of supernumerary centrosomes